Visualization tool for X-ray scanner for sTGC detector production quality control. Issue 1 (January 2016) - Tikhomirov, V O; Filippov, K A; Konovalov, S P; Mikenberg, G; Romaniouk, A; Shchukin, D; Shoa, M; Smakhtin, V; Smirnov, S Yu; Sosnovtsev, V V; Teterin, P E; Tsekhosh, V I; et al.
Abstract: The ATLAS experiment at the Large Hadron Collider has an ambitious program of the detector upgrade to meet an expected rise of accelerator luminosity. The first large system which supposed to be installed in 2019 is the New Small Wheel (NSW) for ATLAS muon spectrometer. In order to ensure high quality and reliability of NSW chambers an X-ray scanning technique is being developed. One of the main components of the X-ray scanner is a special software visualization tool which would allow a fast and clear representation of scanning results and an identification of possible chamber defects.